Integrasi Steam dalam Pembelajaran Matematika untuk Meningkatkan Kreativitas dan Inovasi - Bariyah; Hamimi, Lia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to enhance students' creativity and innovation in mathematics learning through the integration of the STEAM approach at SMP Negeri Unggul Tunas Nusa. The research employed a quantitative experimental method with a one-group pre-test-post-test design. The sample consisted of 25 eighth-grade students from Tunas class. The research instruments included pre-test and post-test assessments to measure students' creativity and innovation. Data analysis was conducted using the Wilcoxon test with the assistance of SPSS software. The analysis results showed a significance value of 0.000 (< 0.05), leading to the rejection of the null hypothesis (H₀) and the acceptance of the alternative hypothesis (H₁). These findings indicate that the integration of the STEAM approach significantly improves students' creativity and innovation in geometry learning. Thus, the STEAM approach can serve as an effective strategy to create more active, creative, and contextual mathematics learning. Keywords: STEAM, Mathematics Learning, Creativity, Innovation.